P638 Nutritional status in paediatric Crohn's disease patients: Does exclusive enteral nutrition help?. (16th January 2018) - Strisciuglio, C; Scarpato, E; Serra, M R; Giugliano, F P; Cenni, S; Mainolfi, C; Martinelli, M; Miele, E
Abstract: Background: Paediatric patients affected by Crohn disease (CD) have an increased risk for low catch-up growth and bone mineralisation disorders, due to the chronic inflammation, the malnutrition, and the malabsorption of nutrients. Our aim was to investigate the impact of exclusive enteral nutrition (EEN) on the nutritional status in a cohort of paediatric CD patients. Methods: CD newly diagnosed patients were prospectively enrolled. At the time of diagnosis (T0), after induction therapy at 8 weeks (T8) and after 24 (T24) weeks from the diagnosis, a complete phisical evaluation was performed together with blood vitamins measurements. The assessment of the fatty free mass (FFM) and the resting energy expediture (REE) was measured through the use of bioelectrical impedance (BIA). Moreover at T0 and at T24 a dual-energy X-ray (DXA) was performed to assess patients' bone mineral density (BMD). Student's t test or a linear regression analysis were performed when needed. Results: Eighteen consecutive CD paediatric patients were enrolled in the study. The median age at diagnosis was 13 years (range: 8–16). Fourteen out of 18 were male (77.8%). All patients started EEN as remission induction therapy. At both time points, and even more significantly at T24, there was a reduction of the activity score of disease ( p < 0.001) and of some main inflammation parameters studied such as the erythrocyte sedimentation rate and platelet count ( p = 0.002 and p < 0.001). There was also an improvement of the z -score for the weight and body mass index (BMI) ( p < 0.001 and p < 0.001) and the tricipital plica measurement ( p = 0.002). At the BIA analysis there was a significant increase of FFM ( p < 0.001) and of REE ( p = 0.002) compared with T0. Moreover, between T0 and T8 there was an improvement of 25OH vitamin D ( p = 0.03), vitamin A ( p = 0.003), E ( p = 0.05), and folate ( p = 0.05) levels. In addition, between T8 and T24 there was also a growth speed rate increase ( p = 0.02). BMD values were increased between T0 and T24, but not significantly. At T0, T8 and T24, FFM was directly related to patients' weight, height, and REE ( p < 0.001). Moreover, at T0 and T24, FFM was also directly correlated to BMD ( p = 0.01 and 0.007). Conclusions: EEN improves the nutritional status in CD children for a sustained period by increasing serum vitamin levels and restoring the patient physical state through an increase of weight, BMI, growth speed and tricipital plica measures. EEN also enhance the FFM and REE, leading to the improvement of the basal metabolism rate. Moreover, in our cohort of patients, the FFM is also directly related to BMD. Even if further studies are needed, our data suggest that FFM could represent a potential safer and indirect measure of children bone metabolism.